Black childhoods: “while one eye cries, the other watches the time” - Conversation circle with Conceição Evaristo - Evaristo, Conceição; Pinto, Cecilia Maria Izidoro; Lima, Fátima; Santos, Abrahão de Oliveira; Baião, Jonê Carla; Oliveira, Luiza (Debates em Educação, 2025)
Between words and shared memories, Conceição Evaristo and the Escrevivencia Collective, formed by Black researchers, discuss black childhoods, escrevivencia and ancestry. Through the author's literary work and memories, reflections emerge on the pain, affection, racism, and inequalities that permeate Black childhoods. At the same time, invention, care, orality, and resistance are highlighted as forces that affirm dignity, identity, and a collective future.